Does education increase risk aversion in households? Some evidence using artefactual experiments in Peru - Alberto Chong; Joan J. Martínez (Latin American Economic Review, 2021)
We provide empirical evidence supporting a causal link between education and risk attitudes when using representative data from representative surveys and artefactual or lab-on-the-field experiments in Lima, Peru. We employ three standard experimental measures of risk attitudes and find that each is positively correlated with years of education. Furthermore, we suggest that this relationship may be causal as we take advantage of an identification strategy that exploits an exogenous boom in the construction of new schools in Lima, providing evidence that more education may increase risk attitudes. Our findings are further confirmed when applying a broad set of robustness tests.
Keywords: D01; O12; 330; Experiments; Surveys; Risk Attitudes; Education; Latin America